Aetiology of permanent childhood hearing loss at a population level. (21st September 2021) - Liddle, Karen; Beswick, Rachael; Fitzgibbons, E Jane; Driscoll, Carlie
Abstract : Aim: To evaluate and describe results of aetiological investigations offered to a population level cohort of babies who had confirmed permanent hearing loss after they either (i) failed universal neonatal hearing screening or (ii) passed newborn screening but were detected with a permanent hearing loss in early childhood. Methods: Descriptive analysis of results of investigations offered to neonates and young children in whom permanent hearing loss was detected as part of a statewide newborn hearing screening programme. A total of 306 285 newborns were screened between 2013 and 2017. The failed screening results were confirmed by a diagnostic audiological assessment battery. Medical evaluation for the identification of the cause of the hearing loss was performed by a paediatrician or otolaryngologist, investigations were ordered using a stepwise approach, and aetiology was assigned using a coding scheme. Results: Permanent hearing loss was confirmed in 967 children (0.3%). Data were available for 873. An aetiological factor was identified or presumed in 61.3% of cases. Genetic causes were present in 26.8% and structural causes were present in 24.9% of cases. Congenital cytomegalovirus was present in 4.4%. Conclusions: Use of a coding scheme is feasible at a population level and allows collation of data from multiple sites and will allow outcome mapping and service planning.